Respuesta :
[tex]m = \frac{y_{2} - y_{1}}{x_{2} - x_{1}} = \frac{5 - (-1)}{-1 - 3} = \frac{5 + 1}{-4} = \frac{6}{-4} = \frac{3}{-2} = -1\frac{1}{2}[/tex]
y - y₁ = m(x - x₁)
y - (-1) = -1¹/₂(x - 3)
y + 1 = -1¹/₂(x) + 1¹/₂(3)
y + 1 = -1¹/₂x + 4¹/₂
- 1 - 1
y = -1¹/₂x + 3¹/₂
4x + y - 2 = 0
+ 2 + 2
4x + y = 2
4x - 4x + y = -4x + 2
y = -4x + 2
y - y₁ = m(x - x₁)
y - (-3) = -4(x - 4)
y + 3 = -4(x) + 4(4)
y + 3 = -4x + 16
- 3 - 3
y = -4x + 13
2x - 3y - 5 = 0
+ 5 + 5
2x - 2x - 3y = -2x + 5
-3y = -2x + 5
-3 -3
y = ²/₃x - 1²/₃
y - (-3) = -1¹/₂(x - 4)
y + 3 = -1¹/₂(x) + 1¹/₂(4)
y + 3 = -1¹/₂x + 6
- 3 - 3
y = -1¹/₂x + 3
y - y₁ = m(x - x₁)
y - (-1) = -1¹/₂(x - 3)
y + 1 = -1¹/₂(x) + 1¹/₂(3)
y + 1 = -1¹/₂x + 4¹/₂
- 1 - 1
y = -1¹/₂x + 3¹/₂
4x + y - 2 = 0
+ 2 + 2
4x + y = 2
4x - 4x + y = -4x + 2
y = -4x + 2
y - y₁ = m(x - x₁)
y - (-3) = -4(x - 4)
y + 3 = -4(x) + 4(4)
y + 3 = -4x + 16
- 3 - 3
y = -4x + 13
2x - 3y - 5 = 0
+ 5 + 5
2x - 2x - 3y = -2x + 5
-3y = -2x + 5
-3 -3
y = ²/₃x - 1²/₃
y - (-3) = -1¹/₂(x - 4)
y + 3 = -1¹/₂(x) + 1¹/₂(4)
y + 3 = -1¹/₂x + 6
- 3 - 3
y = -1¹/₂x + 3